The Relationship between Digital Literacy Skills and Self-Regulated Learning Skills of English Language Education Students - Sari, Elsa; Tungka, Novalita Fransisca (Sintuwu Maroso Journal of English Teaching, 2023)
The purpose of this study is to investigate, among students majoring in English Language Education at Universitas Sintuwu Maroso Poso, the relationship between digital literacy and skills related to self-regulated learning. The participants consisted of 88 students, with a convenient sampling method employed to select a sample size of 85 students. A survey was carried out with the purpose of determining the levels of self-regulated learning and digital literacy skills of the participants. The findings showed that the students performed at moderate levels in both of the domains that were examined. In addition, a favorable but not very strong link was discovered between self-regulated learning skills and digital literacy skills. These findings highlight the significance of understanding the interaction between these two skills and provide EFL educators with insights that may be used to improve effective learning practices among students enrolled in an English Language Education study program.